Development of an affordable soil moisture sensor system with mini-VNA Tiny and smartphone - Zhang, Qiwei; Zainuddin, Mohamad Faiz; Ahmad, Ahmad Fahad; Obays, Susan Jabbar; Abbas, Zulkifly (Universiti Putra Malaysia Press, 2019)
This study attempts to develop a soil moisture measurement system with a monopole antenna sensor, mini-VNA Tiny and a mobile phone respectively. The mini-VNA Tiny is a compact vector network analyzer (VNA) with a USB connection to a smartphone or a tablet. There are 17 sets of data which have been collected from 15 different spots with varying soil moisture content. The actual moisture content on site was collected from TRIME-PICO 64/32 sensor. Upon collection, it was necessary to calibrate the resistance obtained from the mini-VNA between 1 MHz and 3 GHz. The data obtained from the study shows that the resonances of the antenna resistance shift to the left on the frequency spectrum as moisture content increases. A linear model relating the resistance and actual moisture content was developed from this study with coefficient of determination (R2) value of 0.723 at 13 MHz. This value is much less than the anticipated R2 = 0.95 for accurate measurement of soil moisture with monopole antenna at microwave frequency. This could be due to the 0.60 cm thickness of the monopole antenna which may not be suited for soil moisture measurement. Nonetheless, this study demonstrates the potential application of an inexpensive and portable mini-VNA Tiny and smartphone system for sensing applications.